A sensitive, high‐throughput, and ecofriendly method for the determination of lumefantrine, artemether, and its active metabolite dihydroartemisinin by supercritical fluid chromatography and tandem mass spectrometry. Issue 12 (25th May 2018) - Yang, Yinxian; Gao, Hailing; Hou, Shanshan; Su, Ruijuan; Liu, Hongzhuo; Sun, Jin
Abstract: A quick and sensitive supercritical fluid chromatography with tandem mass spectrometry method for the simultaneous determination of lumefantrine, artemether, and its active metabolite dihydroartemisinin in rat plasma was developed and validated. The chromatographic separation was performed on an ACQUITY UPC 2 ™ BEH 2‐EP column within 2.5 min by gradient elution using compressed CO2 and methanol containing 2 mM ammonium acetate as the mobile phases. Detection was achieved by multiple reaction monitoring using electrospray ionization in the positive ionization mode. For sample preparation, 50 μL of the sample was processed by modified high‐throughput, one‐step protein precipitation using hydrogen peroxide as a stabilizer to protect the endoperoxide‐containing artemisinin derivatives from degradation. The calibration curves were linear over the concentration range of 2.0–1000 ng/mL for both artemether and dihydroartemisinin, and 1.0–5000 ng/mL for lumefantrine. The values of selectivity, lower limit of quantification, linearity, accuracy, precision, matrix effects, stability, and recovery met the acceptable range according to the Food and Drug Administration guidelines. The developed method enables high resolution and speed as well as low cost, low solvent consumption, and short time and was successfully applied to pharmacokinetic studies through the intravenous administration of an artemether–lumefantrine lipid emulsion in rats.